PERALATAN TRADISIONAL PENGOLAHAN SAGU DI PULAU SIBERUT, RUPAT, DAN PULAU LINGGA - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2006)
Sago was one of plants which had known by local people who live by hunting. Since the prehistory, this plant type grew well in a jungle so people could use it. The traditional tools that we know today, its technique in heritage